2018
DOI: 10.1093/ofid/ofy210.703
|View full text |Cite
|
Sign up to set email alerts
|

696. Mechanism of Cefiderocol high MIC mutants obtained in non-clinical FoR studies

Abstract: BackgroundCefiderocol (S-649266, CFDC) is a novel siderophore cephalosporin with activity against a wide variety of Gram-negative bacteria including carbapenem-resistant strains. We previously reported that CFDC is efficiently transported into Pseudomonas aeruginosa via iron transporter PiuA. In this study, we examined frequency of resistance of P. aeruginosa to CFDC, and investigated the resistance mechanisms of appeared colonies.MethodsFrequency of resistance (FoR) was determined by plating an overnight cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Previous investigation comparing the frequency of resistance at drug concentrations of 4 × and 10 × the MIC in P. aeruginosa PAO1 strain and detected spontaneous mutation rates of 2.9 × 10 −8 and <7.1 × 10 −9 to cefiderocol, and higher rates of 3.1 × 10 −7 and 3.4 × 10 −7 to ceftazidime, respectively [20]. Mutations in the bacterial iron uptake systems associated with a 4-fold elevated cefiderocol MIC (from 0.5 to 2 μg/mL) were identified in this study, although none of the mutations appeared in the responsible iron transporter gene piuA [32]. The mutations were identified in the upstream regions of pvdS (a gene regulating pyoverdine synthesis), and/or fecI (a gene regulating the ferric citrate transporter, FecA).…”
Section: Mechanism Of Resistancementioning
confidence: 92%
See 1 more Smart Citation
“…Previous investigation comparing the frequency of resistance at drug concentrations of 4 × and 10 × the MIC in P. aeruginosa PAO1 strain and detected spontaneous mutation rates of 2.9 × 10 −8 and <7.1 × 10 −9 to cefiderocol, and higher rates of 3.1 × 10 −7 and 3.4 × 10 −7 to ceftazidime, respectively [20]. Mutations in the bacterial iron uptake systems associated with a 4-fold elevated cefiderocol MIC (from 0.5 to 2 μg/mL) were identified in this study, although none of the mutations appeared in the responsible iron transporter gene piuA [32]. The mutations were identified in the upstream regions of pvdS (a gene regulating pyoverdine synthesis), and/or fecI (a gene regulating the ferric citrate transporter, FecA).…”
Section: Mechanism Of Resistancementioning
confidence: 92%
“…The mutations were identified in the upstream regions of pvdS (a gene regulating pyoverdine synthesis), and/or fecI (a gene regulating the ferric citrate transporter, FecA). These mutations resulted in an overexpression of pyoverdine and FecA protein, respectively, and conferred a 32-fold increase in cefiderocol MICs, whereas ceftazidime MICs were not affected [32]. In another study, the spontaneous mutation rates for 7 strains (ie, 2 multidrug-resistant [MDR] P. aeruginosa [MDRP; 1 IMP-1 producer, 1 ceftazidime resistant], 2 KPC-producing K. pneumoniae , and 3 Enterobacteriaceae [susceptible to ceftazidime-avibactam]) ranged from <1.4 × 10 −8 to 1.6 × 10 −6 for cefiderocol and from <1.0 × 10 −8 to 2.2 × 10 −5 for ceftazidime at drug concentrations of 10 × the MIC [33].…”
Section: Mechanism Of Resistancementioning
confidence: 99%
“…Little is known about the mechanism of resistance of cefiderocol in clinical isolates. Ito et al 57 investigated the frequency of resistance of P aeruginosa isolates to cefiderocol and the mechanism of resistance observed. They demonstrated that the frequency of selecting resistant mutants with cefiderocol was much lower than that observed with ceftazidime at concentrations that were 4 and 10 times the MIC of each these agents.…”
Section: Mechanism Of Resistancementioning
confidence: 99%
“…The siderophore-associated structure of CFDC not only allows a unique mechanism of action, but also opens up the possibility of unique resistance mechanisms not commonly associated with other beta-lactam agents. 54 CFDC's structural characteristics, such as a modified C-3 and modified C-7 side chain, allow itself to withstand hydrolysis by most beta-lactamase enzymes. 25 Importantly, it has been shown that CFDC remains stable against many clinically relevant metallo-and serine-beta-lactamases, including NDMs, KPCs, and OXA-48s.…”
Section: Resistancementioning
confidence: 99%